Pharmacological ascorbate as a novel therapeutic strategy to enhance cancer immunotherapy - Zaher, Amira; Stephens, Laura M.; Miller, Ann M.; Hartwig, Stacey M.; Stolwijk, Jeffrey M.; Petronek, Michael S.; Zacharias, Zeb R.; Wadas, Thaddeus J.; Monga, Varun; Cullen, Joseph J.; Furqan, Muhammad; Houtman, Jon C. D.; et al. (Frontiers in Immunology, 2022)
Pharmacological ascorbate (i.e., intravenous infusions of vitamin C reaching 20 mM in plasma) is under active investigation as an adjuvant to standard of care anti-cancer treatments due to its dual redox roles as an antioxidant in normal tissues and as a prooxidant in cancer cells tissues. Immune checkpoint inhibitors (ICIs) are highly promising therapies for many cancer patients but face several challenges including low response rates, primary or acquired resistance, and toxicity. Ascorbate modulates both innate and adaptive immune functions and plays a key role in maintaining the balance between pro and anti-inflammatory states. Furthermore, the success of pharmacological ascorbate as a radiosensitizer and a chemosensitizer in pre-clinical studies and early phase clinical trials suggests that it may also enhance the efficacy and expand the benefits of ICIs.